2019
DOI: 10.3892/ol.2019.10570
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin 2 inhibits bladder cancer cell proliferation and invasion via the Wnt/β‑catenin pathway

Abstract: The present study aimed to investigate the biological role of the mitochondrial GTPase mitofusin-2 (MFN2) in bladder cancer. MFN2 mRNA expression in tumor and paired adjacent non-tumor tissues from 8 patients was investigated using reverse transcription-quantitative polymerase chain reaction analysis. Immunohistochemistry was used to investigate MFN2 expression in 117 bladder cancer specimens. The associations of MFN2 expression with clinicopathological parameters were evaluated statistically. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…The Wnt/β-catenin signaling pathway has been under attention in recent years due to its role in tumorigenesis [ 115 , 116 , 117 , 118 , 119 ]. The tumor-promoting role of Wnt signaling pathway has been investigated in different cancers, including BC [ 120 , 121 ]. It has been found that Wnt signaling can act as an upstream mediator of EMT, so that after activation of Wnt signaling pathway by certain ligands of Wnt family, GSK-3β activity can be inhibited to facilitate the nuclear translocation of β-catenin.…”
Section: Micrornas Inhibit Emt In Bladder Cancer Cellsmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway has been under attention in recent years due to its role in tumorigenesis [ 115 , 116 , 117 , 118 , 119 ]. The tumor-promoting role of Wnt signaling pathway has been investigated in different cancers, including BC [ 120 , 121 ]. It has been found that Wnt signaling can act as an upstream mediator of EMT, so that after activation of Wnt signaling pathway by certain ligands of Wnt family, GSK-3β activity can be inhibited to facilitate the nuclear translocation of β-catenin.…”
Section: Micrornas Inhibit Emt In Bladder Cancer Cellsmentioning
confidence: 99%
“…Many studies have shown that ERβ is an anti-oncogene in breast cancer and that the loss of ERβ may promote breast cancer occurrence (19,20). As a novel tumor suppressor gene, MFN2 is related to the antitumor activity of many malignant tumors (21)(22)(23). No other studies have provided detailed data or have investigated the effect of ERβ on MFN2 and P-AKT expression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, promising data have been obtained for the development of PI3K/AKT inhibitors in breast cancer and have provided a theoretical basis for the development of PI3K/AKT-targeted inhibitors (36). Although many studies have been performed to determine the relationship between the AKT pathway and breast cancer in recent years (21)(22)(23), none of these studies has demonstrated that the P-AKT signaling pathway is downstream of ERβ/MFN2. Our data indicated that in MCF-7 and MDA-MB-231 human breast cancer cells, ERβ induced the expression of MFN2, while MFN2 reduced P-AKT, and P-AKT was downstream of ERβ/MFN2.…”
Section: Discussionmentioning
confidence: 99%
“…In patients suffering from gastric cancers, a significant increase in the expression of YAP and β-catenin has been correlated to the disease severity [65]. An activation of Wnt/β-catenin signaling has also been associated with the development of colorectal cancer [66], glioblastoma [67] and bladder cancer [68] in patients. Considering the importance of this signaling in different cancers, a Phase II trial has been designed to investigate the safety and efficacy of oral niclosamide, Wnt/β-catenin signaling modulating drug, in colorectal cancer patients [69].…”
Section: Discussionmentioning
confidence: 99%